Penyusunan Laporan Keuangan UMKM Berdasarkan SAK EMKM Pada Usaha Sandra Cake - Ferdawati, Ferdawati; Rahayu, Sri; Heriyanto, Randy; Sulastri, Reni Endang; Haslina, Welsi (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2024)
Financial Accounting Standards for Micro, Small and Medium Entities is one of the Financial Standards established to make it easier for UMKM to prepare and present financial reports that are simpler and easier to understand. The purpose of financial reports for UMKM is to find out exactly how much the company's profits are. This can also make it easier for companies to apply for credit or assistance from the government. This research was carried out at Sandra Cake's business and aims to help companies prepare financial reports in accordance with the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). This research uses interview techniques, documentation and data analysis. The research results show that Sandra Cake still records and processes data manually. The company only has simple records of the number of product sales, so it cannot be known for certain the company's net profit. The main aim of this research is to increase the understanding of business owners and help meet the needs related to UMKM accounting.